Enhancing The Capacity of Art Performances Through The Availability of Artistic Costumes as a Form of Strengthening Tourist Village of Jenisgelaran, Jombang Regency - Rahayu, Anik Cahyaning; Sudarwati; Andari, Novi (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
One of the essential elements in an aesthetic art performance lies in the costumes worn by the performers. Costumes are an urgent supporting aspect in every presentation because they serve as an aesthetic representation that becomes a medium for implementing the distinctive identity of each region. In art performances, costumes function to create visual beauty, distinguish one character from another, depict character traits, provide freedom of movement, and deliver dramatic effects. Thus, costumes are the most important element after artistic movements and musical instruments in a performance. Considering the limitations of available art wardrobes, the lack of contemporary relevance, and the absence of distinctive costume characteristics, solutions to the problems faced by art communities in Jenisgelaran Village need to be provided in the form of funding for artistic costumes that suit the character of each type of art and the age of the performers. Independent ownership of costumes is one of the crucial elements in business management for art groups, as it helps stabilize both individual and group economies. The results of this community service program, funded through the Kemenristek Dikti Grant, are expected to contribute to the economic independence of art performers in the Artist Village of Jenisgelaran, Jombang Regency.